Bibliometric Analysis on Artificial Intelligence Aided Architectural Design - Cengizoglu, Fulya Pelin (Journal of Design Studio, 2024)
Technological advancements have created new dimensions in various fields, including architecture. The widespread use of information technology has particularly transformed architectural designs. In architectural design processes, methods and tools have diversified beyond traditional approaches, incorporating computer-aided programs, computational functions with plugins, and even contemporary artificial intelligence (AI)-supported software and applications tailored to specific needs. It is inevitable that AI-supported designs will increasingly feature in the future of architecture. The purpose of this study is to determine the role of AI applications in architectural design. To this end, a bibliometric analysis was conducted on 137 articles related to artificial intelligence and architectural design from the period 1991-2024, sourced from the Web of Science (WoS) database. The analysis focused on main topics, keywords, authors, sources, highly cited articles, and countries. The selected articles were analyzed using VOSviewer to examine the use of AI applications in architectural design. Quantitative analyses providing an overview of the topic are presented in tables, graphs, and maps. It has been determined that at least 30% of the studies were conducted in the field of architecture. It was found that studies on the subject have rapidly increased since 2020. The continued growth of AI usage across all fields is expected to extend into architectural design as well. Therefore, it is deemed necessary to address AI in architectural design education to align with these advancements. Finally, the paper discusses forward-looking recommendations on how to incorporate AI into architectural design education.